Socio-Scientific Issues Using Two-Tier Instruments Based on Literacy Analysis - Fadhilah, Zahra Ayu; Ulfa, Maria; Indriyanti, Nurma Yunita; Yamtinah, Sri; Shidiq, Ari Syahidul; Mulyani, Bakti; Masykuri, Mohammad (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
Chemical literacy is important for someone to have to understand scientific problems that occur in everyday life so that they can choose wise decisions in solving them. The objectives to be achieved in this study are to analyze the students' chemical literacy skills on acid-base material using a two-tier multiple-choice instrument SSI based. The research design used is a descriptive qualitative method. The sample in this study was taken or selected using a purposive sampling technique. Data collection techniques are used by researchers in the form of tests and interviews. The steps taken to analyze the data are data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that 1. The results of the students' chemical literacy test on acid-base material showed that as many as 15% of students were in the high category, 62% of the students were in the medium category, and 23% of the students were in a low category. 2. Students' chemical literacy was sufficient in the aspect of content (79%), context (70%), HOTS (69%), and attitudes (66%). The sub-indicator that students mastered the most in context indicators was analyzing the strategies and benefits of chemical applications. In the HOTS indicator, the students' most dominant skills are asking questions and seeking information on chemical issues. The attitude indicator shows the lowest achievement among other indicators due to the lack of student interest in issues related to chemistry.